Comparative analysis of chloroplast genomes and phylogenetic analysis of Vitex - XIU Zhiying1, ZHAO Yanling1, CHENG Yongqin2, JIA Yun3, YANG Yanci1* (Guangxi Zhiwu)
Vitex L. is widely distributed in tropical and subtropical areas, mostly as woody trees or shrubs, and contains many plants with medicinal, ornamental and ecological values. To understand the characteristics of Vitex chloroplast genomes, the phylogenetic position and interspecific relationships of the genus, the chloroplast genome sequence of V. agnus-castus was firstly obtained by de novo assembly and annotation, the genome structure, codon preference, high variation region and repeat sequence were then analyzed with 11 published chloroplast genome sequences of Vitex, and then phylogenetic analysis was conducted. The results were as follows:(1)The chloroplast genome of V. agnus-castus was a typically quadripartite structure with a total length of 154 444 bp, in which the length of the large single copy(LSC)region, the small single copy(SSC)region and the inverted repeat(IR)region were 85 229, 17 915 and 51 400 bp, respectively. The chloroplast genome encoded 132 genes, including 87 protein-coding genes, 37 tRNA genes and 8 rRNA genes.(2)The 12 chloroplast genomes of Vitex were highly conserved in terms of genome length, boundary position of IR region, number of encoded genes and GC content.(3)A total of 31 high frequency codons and six common optimal codons were detected in 12 chloroplast genomes of Vitex. Further, the results of ENC-plot, PR2-plot and neutral plot analysis indicated that codon preference was mainly influenced by natural selection.(4)In addition, a total of 14 highly variable regions and 519 simple sequence repeats(SSRs)were detected in the 12 chloroplast genomes of Vitex.(5)The molecular phylogenetic inference in this study supported that Vitex belonged to the subfamily Viticoideae(Lamiaceae), not Verbenaceae. Moreover, phylogenetic inference also provided some understanding of the controversial relationships among V. trifolia, V. bicolor and V. rotundifolia, suggesting that V. rotundifolia was considered as a separate species. This study not only enriches the information of genetic resources of V. agnus-castus, increases the understanding of the chloroplast genomes of Vitex, provides candidate molecular markers for population genetics studies of Vitex, but also proves the effectiveness of chloroplast genome sequence in the phylogenetic reconstruction of Vitex.